Additions to the milliped family Caseyidae. I. Caseya richarti, n. sp., and new records of previously described species in the genus Caseya Cook and Collins 1895 (Diplopoda, Chordeumatida, Caseyidae) - Shear, William A.; Leonard, William P. (Zootaxa, 2007)
Caseya richarti, n. sp., from King Co., Washington, USA, is described from two nearby localities in King County, Washington (state), USA. The genus Caseya Cook and Collins 1895, which now includes 25 species and subspecies, occurs from Los Angeles Co, California, USA, north through the Sierra Nevada and Coast Ranges nearly to the Canadian border. New records are given expanding the range of C. borealis Gardner and Shelley 1989 in Washington, and further new records are provided for Caseya megasoma Gardner and Shelley 1989, C. dorada (Chamberlin 1941), C. heteropa disjuncta Gardner and Shelley 1989, C. heteropa oraria Gardner and Shelley 1989, and C. heteropa montana Gardner and Shelley 1989. Additional notes are provided on gonopod nomenclature and the status of subspecies in Caseya.